Molecular and metabolomic effects of voluntary running wheel activity on skeletal muscle in late middle‐aged rats. Issue 2 (25th February 2015) - Garvey, Sean M.; Russ, David W.; Skelding, Mary B.; Dugle, Janis E.; Edens, Neile K.
Abstract We examined the molecular and metabolomic effects of voluntary running wheel activity in late middle‐aged male Sprague Dawley rats (16–17 months). Rats were assigned either continuous voluntary running wheel access for 8 weeks (RW+) or cage‐matched without running wheel access (RW−). The 9 RW+ rats averaged 83 m/day (range: 8–163 m), yet exhibited both 84% reduced individual body weight gain (4.3 g vs. 26.3 g, P = 0.02) and 6.5% reduced individual average daily food intake (20.6 g vs. 22.0 g, P = 0.09) over the 8 weeks. Hindlimb muscles were harvested following an overnight fast. Muscle weights and myofiber cross‐sectional area showed no difference between groups. Western blots of gastrocnemius muscle lysates with a panel of antibodies suggest that running wheel activity improved oxidative metabolism (53% increase in PGC1α, P = 0.03), increased autophagy (36% increase in LC3B‐II/‐I ratio, P = 0.03), and modulated growth signaling (26% increase in myostatin, P = 0.04). RW+ muscle also showed 43% increased glycogen phosphorylase expression (P = 0.04) and 45% increased glycogen content (P = 0.04). Metabolomic profiling of plantaris and soleus muscles indicated that even low‐volume voluntary running wheel activity is associated with decreases in many long‐chain fatty acids (e.g., palmitoleate, myristoleate, and eicosatrienoate) relative to RW− rats. Relative increases in acylcarnitines and acyl glycerophospholipids were also observed in RW+ plantaris. These data establish that even modest amounts of physical activity during late middle‐age promote extensive metabolic remodeling of skeletal muscle.